Continuous fabrication of polymer microfiber bundles with interconnected microchannels for oil/water separation. (December 2017) - Wang, Yayun; Liu, Xianhu; Lian, Meng; Zheng, Guoqiang; Dai, Kun; Guo, Zhanhu; Liu, Chuntai; Shen, Changyu
Graphical abstract: Highlights: The absorption material (AM) is fabricated by conventional polymer processing method. The as-prepared AM is prepared using low-cost polyolefins in a solvent-free method. The as-prepared AM exhibits excellent reusability. The as-prepared AM shows continuous oil–water separation or oil collection ability. Abstract: Recently, the development of methods for the cleanup of large-scale oil spills or organic pollutants from water has been attracting global attention. However, traditional techniques suffer from the limits of low efficiency and high operation cost. Herein, we propose a high efficiency, large-scale and easy operation approach to fabricate a hydrophobic and oleophilic high density polyethylene microfiber bundles with interconnected microchannels for oil/water separation. The microfiber bundles with high porosity, excellent absorption capacity and large water contact angle are continuously fabricated by a melt extrusion and leaching technique. More importantly, they are readily cleaned by centrifugation and exhibit excellent shape-recoverable property, which are very promising for the cleanup of large-scale oil spills. This study provides a great promising way to fabricate multifunctional polymer materials by using common polymer molding method.